Refusal of Polygamy Permit in Religious Court Decision: Criticism of Gender Justice Against Judge’s Legal Reasoning - Santoso, Lukman; Amaliyah, Arij; Huda, Miftahul (Al-Risalah, 2023)
This study aims to determine and analyse the judges' considerations using gender justice in the Decision of the Madiun District Religious Court Number 1512/Pdt.G/2022/PA.Kab.Mn. Normatively, the permissibility of polygamy rests on the wife's consent and the husband's ability to be fair. In this case, the problem started with applying for a polygamy permit after the Applicant married his second wife. Argumentation: The Applicant, who was married before applying polygamy, was considered unlawful. This is doctrinal legal research with a case, conceptual, and statutory approach. Data sources for this research are court decisions, laws and regulations, books, journals, and research results. This research provides a conceptual basis for judges in making decisions on applications for polygamy licenses based on gender equity so that justice in society is created objectively.